2013
DOI: 10.1589/jpts.25.717
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Rheobase and Chronaxie between the Paretic and Non-Paretic Sides of Hemiplegic Stroke Patients: a Pilot Study

Abstract: [Purpose] Rheobase and chronaxie are used to confirm muscle degeneration. For stroke patients, however, the uses of rheobase and chronaxie in determining paretic side muscle degeneration is not yet fully understood. Thus, in this study, we examined the electrical properties of the quadriceps muscles of stroke patients’ paretic side and compared them with their respective values on the non-paretic side. [Method] The subjects were six stroke patients (three females, three males). The pad of an electrical stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…In this study, the major advantage of the gait trainer with BWS is that it requires less effort by a therapist than conventional therapy. Further scientific studies should be carried out focusing on improvement of gait characteristics and ambulation ability in hemiplegic patients 22 , 23 , 24 , 25 ) . In addition, greater numbers of participants and longer treatment times, including a follow-up, should be used to validate the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the major advantage of the gait trainer with BWS is that it requires less effort by a therapist than conventional therapy. Further scientific studies should be carried out focusing on improvement of gait characteristics and ambulation ability in hemiplegic patients 22 , 23 , 24 , 25 ) . In addition, greater numbers of participants and longer treatment times, including a follow-up, should be used to validate the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we suggest that using Braille can also develop the sensitivity of the median nerve, and this influences the sensitivity of areas innervated by the median nerve. Further systematic studies in the field of physical therapy, such as electrotherapy, neurotherapy, hydrotherapy, and others, are needed 21 , 22 , 23 , 24 ) . In summary, our data could not explain the difference in tactility between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…16 Lower or higher frequencies than occur naturally have been shown to reduce muscle force generation and result in more rapid decline in force generation thought to be due to fatigue. 17 Lee and colleagues 18 showed that muscles affected by stroke require higher amplitude and longer pulse duration of NMES than the non-paretic contralateral muscles.…”
Section: A Hemiplegic Shoulder Subluxationmentioning
confidence: 99%